Allocating taxing powers within the European Union - Schön, Wolfgang; Traversa, Edoardo; Richelle, Isabelle (MPI Studies in Tax Law and Public Finance, 2013)
The contributions to this volume try to overcome the traditional approach of the judicature of the European Court of Justice regarding the application of the fundamental freedoms in direct taxation that is largely built on a non-discrimination test. In this volume, outstanding authors cover various aspects of the national and international tax order when European law meets domestic taxation. This includes testing traditional pillars of income taxation - ability-to-pay, source and residence, abuse of law, arm's length standard - with respect to their place in the emerging European tax order as well as substantial matters of co-existence between different tax systems that are not covered by the non-discrimination approach such as mutual recognition, cross-border loss compensation or avoidance of double taxation. The overarching goal is to flesh out the extent to which a substantive "allocation of taxing powers" within the European Union is on its way to a convincing overall framework and to stretch the discussion "beyond discrimination".